PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM VISUALISASI DAN INOVASI PRODUK KULINER: DAMPAKNYA TERHADAP PERSEPSI DAN PREFERENSI KONSUMEN - Jaya, Unggul Putra (AkMen JURNAL ILMIAH, 2025)
The advancement of Artificial Intelligence (AI) has significantly transformed the culinary industry, particularly in food visualization and product innovation. Visual aesthetics play a crucial role in shaping consumer perceptions and influencing purchase decisions. This study investigates how AI-generated food imagery affects consumer perceptions of quality and purchase intention, and explores consumer responses to AI- assisted culinary product innovations. The research employs a quantitative experimental method with an A/B test design, comparing consumer reactions to AI-generated food images and authentic food photographs without disclosing their sources. Additionally, a consumer survey evaluates perceptions of AI-driven culinary innovations. Findings indicate that AI-generated visuals significantly enhance perceived product quality and attractiveness. However, when consumers are aware that the visuals are AI-generated, purchase intention decreases due to concerns over product authenticity. Despite this, consumers express interest in culinary innovations resulting from human-AI collaboration, provided product safety and authenticity are maintained.